(untitled) (Research, Society and Development, 2022)
Scientific research is the main instrument that enables the advances of science and the progress of humanity; the method is the way to perform the search. However, it is common for academics to face difficulties in understanding and mastering methodologies for research development. The aim of this article is to approach the process of structuring the main methodologies of scientific research adopted in Brazilian universities. This is a bibliographic research, of qualitative character, seeking theoretical support to the proposed discussion. This study is important because it explains important aspects about methodologies in the academic sphere, assisting and guiding the student regarding the standards of research and scientific production. The scientific methodology provides techniques for better performance and quality of scientific production, besides contributing to the critical training and scientific spirit of the researcher.